High–reactive powder concrete on the basis of organic nanomodifikatorov - Shyshkin О.; Brovko, D. (Ways to Improve Construction Efficiency, 2022)
A significant range of organic and mineral binders produced by the industry allows for a wide variety of combinations, providing a variety of resulting compositions. This, in turn, makes it necessary to establish general regularities in the formation of their properties. An attempt is made in this article. The results of studies of the properties of concrete, which are a composition of Portland cement, fine aggregate and mineral–organic complex, intended for the creation of special structures. It is shown that the use of the organic component of the mineral–organic complex of micelle–forming surfactants or polyalcohols leads to the sealing of the inner surfaces of the pores that are formed in concrete, which leads to an increase in the strength of concrete. It has been proven that the most effective use of the mineral is as a mineral component of complex organic compounds containing so–called d–elements, such as iron. The currently widely used mineral–organic compositions of the first type are, as a rule, "mineral binder – organic polymer" or "mineral binder – bitumen (tar)" systems. These types of mineral–organic compositions have undergone quite serious tests and have been tested in operation and have not sufficiently confirmed their effectiveness. But, as you know, these types of organic materials have the disadvantage of aging, which is accompanied by depolymerization (polymer) or a change in structure (asphalts, tars). Therefore, the durability of this type of resistance is limited by the organic component of the mineral–organic composition. It is known that the adsorption properties of derivatives of higher fatty acids depends on the length of the hydrocarbon radical. This is due to the strength of attachment of derivatives of higher fatty acid to the mineral surface. This largely depends on the solubility of the compositions are formed. The solubility of these compounds is, in turn, is determined by the order of solubility of the corresponding salts higher fatty acids. The solubility of these compounds, in turn, determined by the solubility of the respective salts of fatty acids. the authors obtained a mineral–organic material which is a system of "mineral binder based on calcium – fatty acid – a substance containing iron". Mechanism of structure obtained mineral–organic material explained as follows. As is well known, are unsaturated higher fatty acids with two or more double bonds with oxygen independently oxidized.